2009
DOI: 10.1192/bjp.bp.108.051698
|View full text |Cite
|
Sign up to set email alerts
|

In-patient and residential alternatives to standard acute psychiatric wards in England

Abstract: ConclusionsAlternatives to standard acute psychiatric wards represent an important, but previously undocumented and unevaluated, sector of the mental health economy. Further evidence is needed to assess whether they can improve the quality of acute in-patient care. Declaration of interestNone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
85
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 20 publications
(19 reference statements)
1
85
0
Order By: Relevance
“…Poor relationships between staff and service users are frequently reported [6], [7], [8]. Inpatient ward staff identify several barriers to developing therapeutic relationships including: low staffing levels; an associated lack of staff continuity; bureaucratic demands; and uncertainty about the adoption and implementation of therapeutic models [9]. Unsurprisingly, reforming acute care was recently identified as the highest priority of mental health staff and service users in England [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor relationships between staff and service users are frequently reported [6], [7], [8]. Inpatient ward staff identify several barriers to developing therapeutic relationships including: low staffing levels; an associated lack of staff continuity; bureaucratic demands; and uncertainty about the adoption and implementation of therapeutic models [9]. Unsurprisingly, reforming acute care was recently identified as the highest priority of mental health staff and service users in England [10].…”
Section: Introductionmentioning
confidence: 99%
“…Crisis houses tend to be smaller than their hospital counterparts, with a more domestic atmosphere [9], [11]. They are generally well-embedded in the local healthcare system, serving similar populations to inpatient wards, although they rarely admit people compulsorily and fewer people have a history of violence [9], [11]. Force, restraint and seclusion are rarely used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of recovery-oriented staff training in community-based settings have shown positive changes in staff attitudes (9). Evaluations of the recovery-orientation of mental health services have focused on outpatient and rehabilitative facilities rather than inpatient facilities (10,11). Moreover, the recovery-orientation among staff in psychiatric hospitals appears to be lower than that in community settings (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Fifty years of deinstitutionalization of psychiatric care have produced creative alternatives to the inpatient ward as the locus of treatment [1,2]. Options available to the acutely ill include expanded community mental health care facilities and mobile treatment teams such as assertive community treatment (ACT) [3].…”
Section: Introductionmentioning
confidence: 99%